Help-seeking in the event of psychological distress: a qualitative exploration - Brown, Susan (2013)
Aim This thesis explores the seeking of help from a General Practitioner in the event of psychological distress. The study explores help-seeking, lay understanding around mental health, and the relationship between the two.